Diagnostic Accuracy of Ultrasound in Abdominal Organ Injury, Nakornping Hospital - Moonrintah, Suntharee (Journal of Health Science of Thailand, 2018)
The objective of this diagnostic test and descriptive study was to evaluate the accuracy of abdominal ultrasonography (US) in patients with abdominal trauma. A retrospective review of medical record and imaging of patients with abdominal trauma, investigated by US at Nakornping hospital from 1 October 2003 to 31 August 2006. Results of US compared with surgical results and/or clinical courses to determine diagnostic accuracy. In all, 290 patients were included in the study and showed a sensitivity of 62.5 percent, specificity of 100 percent, positive predictive value (PPV) of 100 percent, negative predictive value (NPV) of 1.4 percent and false negative rate (FNR) of 36.5 percent. Highest sensitivity and negative predictive value were reported in diagnosis of kidney trauma while those of pancreas, urinary bladder and gallbladder could be diagnosed with the highest specificity and positive predictive value. However, the false negative rate was high in the order of gallbladder, bowel, pancreas and urinary bladder. Positive US results were significant predictors for surgical treatment (p<0.001). Abdominal organ injuries were confirmed in the operation that followed in the cases of ascites patients 1.7 times higher than those of the non - ascites patients. Abdominal US is useful in screening for injury in patients with abdominal trauma. Awareness of ascites in the US result is critical as many patients possibly have intra abdominal organ injuries. It should be noted that ascites, identified by US, in patients with abdominal trauma are good predictors of intra-abdominal organ injuries.